The Moderating Effect of the Islamic Approach on the Relationship Between Public Relations Roles and Crisis Communication Strategies in Yemen - Al-Akwa'a, Ebrahim Mohammed Abdullah (2012)
The general aim of this study is to investigate the role of public relations in crisis management in public and private organizations in Yemen. Specifically, the study examines the relationship among public relations role, crisis communication strategy and organizational culture in managing crisis and determines whether there is any differences between public and private organizations in Yemen in terms of public relations role, crisis communication strategies, organizational culture and crisis management. The study also examines the moderating effects of Islamic approach on public relations role, crisis communication strategies, organizational culture and crisis management. The study employs a survey research design. The data is collected through questionnaires administered to 200 public relations managers; 73% from public organizations and 27% from private organizations in Yemen. The study uses correlation and regression analyses to analyze the data. The findings indicate that public relations role, crisis communication strategy, and organizational culture are positively related to crisis management. In addition, the Islamic approach has been found to partially moderate the relationship among public relations role, crisis communication strategy, organizational culture and crisis management. However, the study does not find any significant differences between public and private organizations in Yemen in terms of public relations role, crisis communication strategy, organizational culture and crisis management. Based on the results of this study, it is recommended that further research be undertaken using qualitative research methodology to understand better the relationship among public relations role, crisis communications strategy, organizational culture and crisis management. It is also recommended that further research be conducted to explore the dimensions of the Islamic approach as a moderating variable to determine its effects in relation to public relations role and crisis management.